A Potential Role of Coumestrol in Soybean Leaf Senescence and Its Interaction With Phytohormones - Mun, Bong-Gyu; Kim, Hyun-Ho; Yuk, Heung Joo; Hussain, Adil; Loake, Gary John; Yun, Byung-Wook (Frontiers in Plant Science, 2021)
Coumestrol is a natural organic compound synthesized in soy leaves and functions as a phytoalexin. The coumestrol levels in plants are reported to increase upon insect attack. This study investigates the correlation between coumestrol, senescence, and the effect of phytohormones on the coumestrol levels in soybean leaves. Our analysis involving high-performance liquid chromatography and 2-D gel electrophoresis indicated a significant difference in the biochemical composition of soybean leaves at various young and mature growth stages. Eight chemical compounds were specifically detected in young leaves (V1) only, whereas three different coumestans isotrifoliol, coumestrol, and phaseol were detected only in mature, yellow leaves of the R6 and R7 growth stage. MALDI-TOF-MS analysis was used to identify two proteins 3,9 -dihydroxypterocarpan 6A-monooxygenase (CYP93A1) and isoflavone reductase homolog 2 (IFR2) only in mature leaves, which are key components of the coumestrol biosynthetic pathway. This indicates that senescence in soybean is linked to the accumulation of coumestrol. Following the external application of coumestrol, the detached V1-stage young leaves turned yellow and showed an interesting development of roots at the base of the midrib. Additionally, the application of phytohormones, including SA, MeJA, and ethephon alone and in various combinations induced yellowing within five days of the application with a concomitant significant increase in endogenous coumestrol accumulation. This was also accompanied by a significant increase in the expression of genes CYP81E28 (Gm08G089500), CYP81E22 (Gm16G149300), GmIFS1, and GmIFS2. These results indicate that various coumestans, especially coumestrol, regulate leaf maturity or senescence in soybean.